2022
DOI: 10.1017/mit.2022.55
|View full text |Cite
|
Sign up to set email alerts
|

Right-wing extremism and lone-actor violence in Italy: the case of the 2018 Macerata shooting

Abstract: On 3 February 2018, in the town of Macerata, an Italian citizen with far-right sympathies deliberately fired several shots from his car at nine African immigrants, injuring six. The article argues that this shooting can be considered an act of lone-actor terrorism, an anomaly in the Italian context. Based on the social science literature on this subject, the paper analyses the profile of the shooter and the dynamics of the attack. Moreover, adopting a relational perspective to radicalisation, it examines the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Psychologist Peter Suedfeld (2004) observed that, quite surprisingly, terrorists not infrequently end up revealing intentionally their identity, even at the risk of causing disastrous consequences for themselves (see Schuurman et al., 2018; Dudenhoefer et al., 2021; Rose and Morrison, 2021; cf. Marone, 2023) and for their organisation. This act can be driven by both “positive” motivations, connected to excitement and ego‐enhancement (eagerness to display power and feeling of superiority, desire to express intimate values, etc.)…”
Section: Boundaries and Barriers Of External Secrecymentioning
confidence: 99%
“…Psychologist Peter Suedfeld (2004) observed that, quite surprisingly, terrorists not infrequently end up revealing intentionally their identity, even at the risk of causing disastrous consequences for themselves (see Schuurman et al., 2018; Dudenhoefer et al., 2021; Rose and Morrison, 2021; cf. Marone, 2023) and for their organisation. This act can be driven by both “positive” motivations, connected to excitement and ego‐enhancement (eagerness to display power and feeling of superiority, desire to express intimate values, etc.)…”
Section: Boundaries and Barriers Of External Secrecymentioning
confidence: 99%